Physiotherapy Management of Left Anterior Cruciate Ligament (ACL) Injury Using Electrical Stimulation and Exercise Therapy at ABR Physiotherapy Clinic, Bojonegoro - Dimas Arya Nugraha; Diah Rosyida Maulidina; Halim Warda (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Anterior Cruciate Ligament (ACL) injuries are commonly caused by non-contact mechanisms related to muscle imbalance in supporting the knee, decreased flexibility, reduced muscle strength and endurance, poor joint coordination, and external pressure. ACL injuries can be treated operatively through reconstructive procedures. However, post-operative conditions following ACL reconstruction often lead to complications such as pain, inflammation, muscle atrophy, limited range of motion (ROM), and decreased lower limb muscle strength, which can delay functional recovery. Physiotherapy plays a crucial role in the rehabilitation process to restore knee function. This study aims to describe the physiotherapy management in post-operative ACL patients in reducing pain, improving muscle strength, enhancing joint range of motion, and increasing functional activity. The method used was a case study involving one post-operative ACL patient at ABR Physiotherapy Clinic in Bojonegoro who underwent therapy from January 6 to January 23, 2025. Interventions included Electrical Stimulation (ES) and therapeutic exercise, with data collected using the Numerical Rating Scale (NRS), Range of Motion (ROM), segmental circumference, Manual Muscle Testing (MMT), and the Lower Extremity Functional Scale (LEFS). The results showed a decrease in tenderness pain from a score of 2 to 0, motion pain from 2 to 0, an increase in knee flexion from 120° to 130°, extension from 10° to 5°, an improvement in muscle strength from 4 to 5 in the left knee, and an increase in functional activity score from 40 to 41. The conclusion of this study is that Electrical Stimulation and therapeutic exercise are effective in reducing pain, improving range of motion, enhancing muscle strength, and increasing functional activity in post-operative ACL patients.